2021
DOI: 10.1002/1873-3468.14029
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of RNA–protein interactions in TNF‐α induced alternative splicing in metabolic disorders

Abstract: In this report, using the database of RNA-binding protein specificities (RBPDB) and our previously published RNA-seq data, we analyzed the interactions between RNA and RNA-binding proteins to decipher the role of alternative splicing in metabolic disorders induced by TNF-a. We identified 13 395 unique RNA-RBP interactions, including 385 unique RNA motifs and 35 RBPs, some of which (including MBNL-1 and 3, ZFP36, ZRANB2, and SNRPA) are transcriptionally regulated by TNF-a. In addition to some previously reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In the process of cell activation and differentiation, the cell will adjust its own energy metabolism according to the actual consumption. The body is a complete concept, and its metabolic disorders affect the function of every cell that makes up the organism (140,141). Therefore, the damage of bone or cartilage integrity in patients with hyperglycemia can be explained by energy metabolism (142)(143)(144).…”
Section: Energy Metabolismmentioning
confidence: 99%
“…In the process of cell activation and differentiation, the cell will adjust its own energy metabolism according to the actual consumption. The body is a complete concept, and its metabolic disorders affect the function of every cell that makes up the organism (140,141). Therefore, the damage of bone or cartilage integrity in patients with hyperglycemia can be explained by energy metabolism (142)(143)(144).…”
Section: Energy Metabolismmentioning
confidence: 99%
“…TTP has been reported to control the TNF-α level through binding to the AU-rich element region of TNF-α mRNA (59). TTP can also be upregulated by TNF-α treatment (60). Therefore, we theorize that TTP and TNF-α reciprocally regulate each other and play a crucial role in inflammation and metabolic disturbance.…”
Section: Tristetraprolinmentioning
confidence: 90%
“…Researchers recently discovered that tumor necrosis factor-alpha (TNF-α), which is a proinflammatory cytokine and a crucial contributor to various metabolic syndromes, modulates the expression of MBNL [68,69]. MBNL1 and 3 exhibited a significant reduction at the transcriptional level in cells under TNF-a-induced metabolic stress [69].…”
Section: Therapies To Alleviate Mbnl Sequestration or Overexpress Mbnlmentioning
confidence: 99%
“…Researchers recently discovered that tumor necrosis factor-alpha (TNF-α), which is a proinflammatory cytokine and a crucial contributor to various metabolic syndromes, modulates the expression of MBNL [68,69]. MBNL1 and 3 exhibited a significant reduction at the transcriptional level in cells under TNF-a-induced metabolic stress [69]. Previous studies showed high glucose induces TNF-α expression [70] and MBNL1 expression was reduced under high-glucose conditions [71], which strengthens the role of TNF-α in regulating MBNL expression.…”
Section: Therapies To Alleviate Mbnl Sequestration or Overexpress Mbnlmentioning
confidence: 99%